An investigation into semantic and pragmatic features of hyperbole used in football commentaries in english and vietnamese newspapers - Cao Nguyễn Minh Thông (2015)
This thesis aims to find out the semantic and pragmatic features of hyperbole used in football commentaries in English and Vietnamese newspapers, and to help Vietnamese learners of English achieve comprehensive understanding of hyperbole in both English and Vietnamese. For the purpose, both descriptive and contrastive methods were used combined with the qualitative and quantitative approaches in the thesis. The findings of this study were presented based on a collection of 700 hyperboles in English and Vietnamese (350 hyperboles for each language) from online newspapers. From the study‘s results, the thesis gave a remarkably detailed description of semantic and pragmatic features of hyperboles used in football commentaries in English and Vietnamese newspapers. The findings also pointed out similar points of English and Vietnamese hyperboles such as most of hyperboles in English and Vietnamese share the same in some typical topics, and they are used with the same purposes with 6 functions for football commentaries; emphasizing, complimenting, complaining, criticizing, admiring and mocking. Along with the similarities, interestingly different features underlying cultural features were found as well. Based on the result of data analysis, some implications and suggestions comprehending and using hyperbole in football commentaries effectively were given to Vietnamese students of English and those who are interested in writing football commentaries.